Effect of heat treatment and addition of 4-META to silane on microtensile bond strength of IPS e.max CAD ceramic to resin cement - Laleh Soleimani; Homayoon Alaghemand; Seyyed Mostafa Fatemi; Behnaz Esmaeili (Wolters Kluwer Medknow Publications, 2019)
Background: Silane promotes bonding between ceramic and resin cement. Silane function could be improved by heat treatment and adding 4-Methacryloxyethyl trimellitate anhydride (4-META). The aim of this study was to assess the effect of heat treatment and adding 4-META to silanes on the microtensile bond strength of IPS e.max CAD ceramic and resin cement. Materials and Methods: In this in vitro study, 32 IPS e.max CAD blocks (6 mm × 6 mm × 4 mm) were randomly divided into 8 groups of 4. The ceramic surfaces were etched by 10% hydrofluoric (HF) for 20 s, and Clearfil Ceramic Primer Plus, Clearfil Porcelain Bond Activator (CPA) +4-META, CPA + Clearfil SE Bond (CPA + SE), and Bis-Silane with and without Oven drying at 100°C for 5 min were applied on the ceramic surfaces as silanes, and then, the ceramics were bonded to composite disks by dual-cured resin cements. Ultimately, a total of 120 sticks ( 1 mm × 1 mm × 8 mm) were subjected to microtensile bond strength test (15 sticks from each group) and the failure types were assessed by stereomicroscope at 40x. Data were analyzed by two-sided analysis of variance test and Student's t-test the P values were considered to be < 0.05. Results: The Bis Silane group (two bottles) showed maximum bond strength (P = 0.009). Heat treatment significantly reduced the bond strength in Bis Silane (P = 0.0001); but, in other groups, it did not show significant effect on the bond strength. Adding 4-META to CPA did not significantly affect the microtensile bond strength of IPS e.max CAD ceramic to resin cement, and there was no difference in mode of failure between groups. Conclusion: The effect of silane type was significant on the microtensile bond strength of the ceramic to resin cement. The effect of 4-META on the bond strength was not significant. The interaction between silane type and heat treatment on the bond strength of ceramic to resin cement was also significant.